Prethrombin-1 as a Drug Substance Promoting Hemostasis with Reduced Risk of Thrombosis - Graus, Johann Georg; Prückler, Michael; Bergmeister, Helga; Mader, Christoph; Trefilov, Alexandru; Gölles, Richard; Kunschak, Marianne; Schramm, Wolfgang (Thrombosis and Haemostasis, 2024)
Introduction Prethrombin-1 is a Gla-domain lacking enzymatically inactive split product that results from the cleavage of fragment 1 from prothrombin by thrombin in a feedback reaction.Methods A prethrombin-1 preparation derived from human plasma was tested for its hemostatic and thrombogenic properties. Animal models of nail clipping (for rabbits) and tail clipping (for mice) were developed to measure blood loss in FVIII-inhibitor or rivaroxaban anticoagulated rabbits and mice, respectively. A modified Wessler test was used in rabbits to assess the thrombogenic potential by Wessler score and clot weight. Studies were performed in groups of three to six for prethrombin-1 dose escalation and comparison with prothrombin, Beriplex®, FEIBA®, and saline as a control. Data were analyzed using t-statistics or the Mann Whitney U test as applicable.Results Prethrombin-1 has excellent hemostatic properties in anticoagulated mouse and rabbit bleeding models. Wessler tests suggest that in contrast to activated and nonactivated prothrombin complexes, prethrombin-1 has negligible thrombogenic potential.Conclusion The thrombin zymogen prethrombin-1 promotes hemostasis with reduced risk of thrombosis. Prethrombin-1 may have potential to become a life-saving treatment for patients who bleed or are at risk of bleeding.
Keywords: coagulation; vitamin K-dependent proenzyme; clotting factors; prothrombin; prethrombin-1